Farmers’ Preferences of Improved Wheat Varieties in Wheat Subsector Kailali, Nepal - Bhatt, Prashant; Bist, Pratibha; Ojha, Laxmi Narayan (International Journal of Applied Sciences and Biotechnology, 2020)
Kailali is the second highest district regarding wheat production and area coverage. A study was carried out in the Kailali district for preference of farmers on different wheat varieties that were being cultivated in the district. The objective of the study was to assess farmers’ preference and perception on the different improved wheat varieties in the area. Five commonly grown wheat varieties and seventeen important wheat varietal traits were selected through focus group discussion, key informant interview and preliminary survey. Sixty households were selected for face-to-face personal interview, twelve for each selected variety, at random from Ghodaghodi Municipality, Gauriganga Municipality and Kailari Rural Municipality of Kailali. The weightage of the seventeen selected traits were determined using an online survey conducted among individuals from different designation with the agricultural background who were well known about wheat cultivation practices in Kailali district. Yield, flour quality and tillering were found to be the trait of higher weightage and stem thickness was the trait of lowest weightage. The preferences of the farmers were measured using wheat preference index (WPI). The varieties Vijay, NL-971, HD-2967, Gautam and Aditya were ranked as I, II, III, IV and V respectively. The incorporation of farmers' preferred traits in future wheat varieties would increase the likelihood of adoption of the varieties. Similarly, proper participatory field trial of new improved wheat varieties would also help in the selection of the suitable varieties in the area concerning the farmers’ criteria of selection. Int. J. Appl. Sci. Biotechnol. Vol 8(4): 432-436